The concept of the okadaic acid class of tumor promoters is revived in endogenous protein inhibitors of protein phosphatase 2A, SET and CIP2A, in human cancers - Fujiki, Hirota (J Cancer Res Clin Oncol, 2018)
PURPOSE: The okadaic acid class of tumor promoters, which are inhibitors of protein phosphatases 1 and 2A (PP1 and PP2A), induced tumor promotion in mouse skin, rat glandular stomach, and rat liver. Endogenous protein inhibitors of PP2A, SET and CIP2A, were up-regulated in various human cancers, so it is vital to review the essential mechanisms of tumor promotion by the okadaic acid class compounds, together with cancer progression by SET and CIP2A in humans. RESULTS AND DISCUSSION: The first part of this review introduces the okadaic acid class compounds and the mechanism of tumor promotion: (1) inhibition of PP1 and PP2A activities of the okadaic acid class compounds; (2) some topics of tumor promotion; (3) TNF-α gene expression as a central mediator in tumor promotion; (4) exposure to the okadaic acid class of tumor promoters in relation to human cancer. The second part emphasizes the overexpression of SET and CIP2A in cancer progression, and the anticancer activity of SET antagonists as follows: (5) isolation and characterization of SET; (6) isolation and characterization of CIP2A; (7) progression of leukemia with SET; (8) progression of breast cancer with SET and CIP2A; (9) progression of lung cancer with SET; (10) anti-carcinogenic effects of SET antagonists OP449 and FTY720; and also (11) TNF-α-inducing protein of Helicobacter pylori, which is a clinical example of the okadaic acid pathway. CONCLUSIONS: The overexpression of endogenous protein inhibitors of PP2A, SET and CIP2A, is tightly linked to the progression of various human cancers, as well as Alzheimer’s disease.